Temporal sweetness and side tastes profiles of 16 sweeteners using temporal check-all-that-apply (TCATA). (July 2019) - Tan, Vicki Wei Kee; Wee, May Sui Mei; Tomic, Oliver; Forde, Ciaran G.
Abstract: An increase in consumer awareness around the negative health impacts of consuming excess added sugars has led to a rise in the replacement of sucrose in foods and beverages. This replacement is often through the use of low or no calorie sweeteners to reduce total calories while maintaining sweetness and palatability. There are a wide variety of sweeteners with diverse physical and caloric compositions which can be used at concentrations estimated to be equi-sweet to sucrose in food products. However, many of the available sweeteners are known to differ in their temporal profiles and may have other side and aftertastes alongside sweetness that need to be considered when comparing their suitability as potential sucrose substitutes. The objective of the current study was to profile and compare the temporal sweetness and qualitative differences of 15 sweeteners to sucrose across nutritive saccharide (sucrose, dextrose, fructose, allulose (D-psicose), palatinose (isomaltulose), sucrose-allulose mixture), nutritive polyol (maltitol, erythritol, mannitol, xylitol, sorbitol) and non-nutritive (acesulfame-k, aspartame, sucralose, stevia (rebaudioside-A or rebA), luo han guo (monk fruit extract or mogroside)) groups, at equi-sweet intensity to 10% w / v sucrose based on a previous psychophysical dose-response study. Using the Temporal Check-all-that-Apply (TCATA) method, 20 participants evaluated a set of 17 sweetener samples (including a sucrose duplicate) in triplicates across three 1-h sessions for the occurrence of six attributes (sweetness, bitterness, metallic taste, chemical taste, honey taste and mouth-drying) over a 60 s period. Sucrose was characterised by a rapid sweetness onset (within first 10 s) to peak citation, and subsequent decay of sweetness with minimal side tastes noted. Acesulfame-K, stevia (rebA) and luo han guo had prominent and long-lasting citations of the undesirable bitter, metallic and chemical side tastes and significantly lower sweetness citations. Allulose, erythritol, sorbitol, aspartame and sucralose were perceived to have bitter, metallic and chemical side tastes, but retained a largely sweet taste profile, with longer residual sweetness for aspartame and sucralose. Nutritive sweeteners dextrose, fructose, maltitol, mannitol, sucrose-allulose mixture, palatinose and xylitol had the most similar temporal and qualitative taste profiles when compared to sucrose, in terms of their sweetness onset, peak sweetness citations, sweetness decay, and side taste profiles. Graphical abstract: Unlabelled Image Highlights: TCATA was used to compare temporal profiles of sweeteners. Nutritive sweeteners had similar sweetness and side-taste profiles to sucrose. Non-nutritive sweeteners had temporal profiles that varied most from sucrose. Sucrose-allulose mixture (1:1) had similar temporal profile to sucrose. TCATA provides dynamic sensory information useful in substituting sucrose.